Mixed-methods pre-match cooling improves simulated soccer performance in the heat - Aldous, J. W. F.; Chrismas, B. C. R.; Akubat, I.; Stringer, C. A.; Abt, G.; Taylor, L. (European Journal of Sport Science, 2019)
This investigation examined the effects of three pre-match and half-time cooling manoeuvres on physical performance and associated physiological and perceptual responses in eight University soccer players during a non-motorised treadmill based individualised soccer-specific simulation [intermittent soccer performance test (iSPT)] at 30°C. Four randomised experimental trials were completed; following 30-min (pre-match) and 15-min (half-time) cooling manoeuvres via (1) ice slurry ingestion (SLURRY); (2) ice-packs placed on the quadriceps and hamstrings (PACKS); (3) mixed-methods (MM; PACKS and SLURRY concurrently); or no-cooling (CON). In iSPT first half, a moderate increase in total (Mean ± Standard Deviation: 108 ± 57 m, qualitative inference: most likely, Cohen`s d: 0.87, 90%CL: ±0.31), high-speed (56 ± 46 m, very likely, 0.68 ± 0.38) and variable run (15 ± 5 m, very likely, 0.81 ± 0.47) distance covered was reported in MM compared with CON. Additionally, pre-match reductions in thermal sensation (-1.0 ± 0.5, most likely, -0.91 ± 0.36), rectal (-0.6 ± 0.1°C, very likely, -0.86 ± 0.35) and skin temperature (-1.1 ± 0.3°C, very likely, -0.88 ± 0.42) continued throughout iSPT first half. Physical performance during iSPT first half was unaltered in SLURRY and PACKS compared to CON. Rectal temperature was moderately increased in SLURRY at 45-min (0.2 ± 0.1°C, very likely, 0.67 ± 0.36). Condition did not influence any measure in iSPT second half compared to CON. Only MM pre-match cooling augmented physical performance during iSPT first half, likely due to peripheral and central thermoregulatory factors favourably influencing first half iSPT performance. Further practical half-time cooling manoeuvres which enhance second half performance are still required.